2023
DOI: 10.1002/acr.25139
|View full text |Cite
|
Sign up to set email alerts
|

Validity, Reliability, and Differential Item Functioning of English and French Versions of the 10‐Item Connor‐Davidson Resilience Scale in Systemic Sclerosis: A Scleroderma Patient‐Centered Intervention Network Cohort Study

Abstract: ObjectiveSome individuals with systemic sclerosis (SSc) report positive mental health, despite severe disease manifestations, which may be associated with resilience, but no resilience measure has been validated in SSc. This study was undertaken to assess the validity, reliability, and differential item functioning (DIF) between English‐ and French‐language versions of the 10‐item Connor‐Davidson Resilience Scale (CD‐RISC‐10) in SSc.MethodsEligible participants were enrolled in the Scleroderma Patient‐centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The results of our CFA are consistent with the findings of other studies confirming the single-factor model of the tool. Numerous studies support our finding that the CD-RISC-10 is a unidimensional tool for measuring resilience [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Our study investigated, for the first time, the validity of the CD-RISC-10 using a sample of nurses.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results of our CFA are consistent with the findings of other studies confirming the single-factor model of the tool. Numerous studies support our finding that the CD-RISC-10 is a unidimensional tool for measuring resilience [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Our study investigated, for the first time, the validity of the CD-RISC-10 using a sample of nurses.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the single-factor model of the CD-RISC-10 is strongly supported since it has been found in studies on different countries (e.g., the USA, the UK, China, France, Spain, Iran, and Nigeria) with different study populations (e.g., healthy individuals, chronic patients, young adults, and older adults). Additionally, a considerable number of studies have suggested that CD-RISC-10 has good convergent criteria and divergent validity when using a variety of tools measuring social support, self-efficacy, self-esteem, mastery, mental health, depression, and anxiety [ 50 , 51 , 53 , 54 , 55 , 56 , 57 ]. For instance, Neyer et al found a strong positive correlation (r = 0.78) between CD-RISC-10 and another tool that measures resilience, namely, the 14-item Resilience Scale [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations